PEMODELAN KENDAll LOGIKA FUZZY (FUZZY LOGIC CONTROLLER) PADA PERANGKAT PEMINDAI GAMMA - Arjoni Amir (Jurnal Perangkat Nuklir, 2010)
MODELING OF FUZZY LOGIC CONTROLLER ON GAMMA SCANNING DEVICE. Modeling and simuletion of controller to set the high position and direction of the source of gamma radiation isotope Co-60 and Nal(TL) detector of gamma scanning device by using fuzzy logic controller, FLC has been done. The high positions and in the right direction of gamma radiation and Nal (TI) detector obtained the optimal enumeration. The counting data obtained from gamma scanning device counting system is affected by the instability of high position and direction of the gamma radiation source and Nal(T1)detector or the height and direction are not equal between the gamma radiation source and Nal(TI)detector. Assumed a high position and direction of radiation sources can be fixed while the high position detector h (2, 1,0, -1, -2) can be adjusted up and down and the detector can be changed direction to the left or right angle w (2, 1 , 0, -1, -2) when the position and direction are no longer aligned with the direction of the source of gamma radiation, the counting results obtained will not be optimal. Movement detector direction towards the left or right and the high detector arranged by the DC motor using fuzzy logic control in order to obtain the amount of output fuzzy logic control which forms the optimal output quantity count. The variation of height difference h between the source position of the gamma radiation detector and change direction with the detector angle w becomes the input variable membership function (member function) whereas the fuzzy logic for the output variable membership function of fuzzy logic control output is selected scale fuzzy logic is directly proportional to the amount of optimal counting. From the simulation results obtained by the relationship between the amount of data output variable of fuzzy logic controller with the amount of data input variable height h and direction detector w is depicted in graphical form surface.  PEMODELAN KENDALl LOGIKA FUZZY (FUZZY LOGIC CONTROLLER) PADA PERANGKA T PEMINDAI GAMMA. Telah dilakukan pemodelan dan simulasi kendali untuk mengatur posisi tinggi dan arah sumber radiasi gamma isotop Co-60 dan detektor Nal(TL) perangkat pemindai gamma dengan menggunakan metode kendali logika fuzzy (fuzzy logic controller, FLC). Dengan posisi tin'ggi dan arah yang benar dari radiasi gamma dan detector Nal(TI) diperoleh hasil pencacahan yang optimal. Data pencacahan yang diperoleh dari sistem pencacahan perangkat pemindai gamma dipengaruhi oleh ketidakstabilan posisi tinggi dan arah antara sumber radiasi gamma dan detektor Nal(TI) atau ketinggian dan arah yang tidak sama antara sumber radiasi gamma dan detektor Nal(TI). Diasumsikan posisi tinggi dan arah sumber radiasi bisa diatur tetap sedangkan posisi tinggi detektor h (+2,+1,0,-1,-2) dapat diatur naik-turun dan arah detektor dapat diubah arah ke kiri atau kanan membentuk sudut w (+2, +1,0,-1,-2) bila posisi dan arah tersebut tidak segaris lagi dengan arah sumber radiasi gamma maka hasil pencacahan yang diperoleh tidak akan optimal. Gerakan arah detektor kearah kiri atau kanan dan tinggi detektor diatur sedemikian rupa oleh motor DC dengan menggunakan kendali logika fuzzy sehingga diperoleh keluaran besaran kendali logika fuzzy yan